Mitochondrial metabolism: Inducer or therapeutic target in tumor immune-resistance?. (February 2020) - Kopecka, Joanna; Gazzano, Elena; Castella, Barbara; Salaroglio, Iris C.; Mungo, Eleonora; Massaia, Massimo; Riganti, Chiara
Highlights: Metabolites released from mitochondria help cancer cells to evade immune system. Effector and immune-suppressive cells have a different mitochondria metabolism. Targeting mitochondria metabolism in cancer cells can reverse immune-resistance. Modulating mitochondria metabolism activate or suppress immune cells activity. A precision medicine targeting mitochondria of cancer or immune subsets is needed. Abstract: Mitochondria have been considered for a long time only as the principal source of building blocks and energy upon aerobic conditions. Recently they emerged as key players in cell proliferation, invasion and resistance to therapy. The most aggressive tumors are able to evade the immune-surveillance. Alterations in the mitochondria metabolism either in cancer cells or in host immune system cells are involved in such tumor-induced immune-suppression. This review will focus on the main mitochondrial dysfunctions in tumor and immune cell populations determining immune-resistance, and on the therapies that may target mitochondrial metabolism and restore a powerful anti-tumor immune-activity.